ANALSIS BERFIKIR POSITIF DALAM BELAJAR PADA SISWA KELAS XI MA ISLAMIYAH PONTIANAK TAHUN 2022/2023 - Andriani, Indah; Astuti, Indri; Fergina, Ana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this research was to find out about positive thinking in learning in Class XI students at MA IslamiyahPontianak. The problem of this research is how to think positively in learning in class XI students of MA Islamiyah Pontianak. This research uses the descriptive method in the form of a survey study. The population is 46 students of class XI MA Islamiyah Pontianak. The research technique uses indirect communication as a data collection tool in data of questionnaire statement. Data analysis techniques are performed by statistical calculations using the percentage formula. The results of the research on positive thinking in learning in class XI students at MA Islamiyah Pontianak by obtaining a percentage of 60.23% reached the "Moderate" category of loading thoughts with the percentages of 56.14% in the category "Medium" the use of obtained the percentages of 61.14% received the category " Moderate" control of the mind gets the percentages of 62.72% in the "Moderate" category. So the conclusion of this research is the positive thinking in learning in class XI students of MA Islamiyah Pontianak by achieving a total percentage of 60.23% gets in the category "Medium"